Women, nature, and development in sites of Ecuador's petroleum circuit. Issue 1 (January 2016) - Cielo, Cristina; Coba, Lisset; Vallejo, Ivette
Abstract : This article argues that the contradictory character of Ecuador's current development project is made evident through a focus on energy resource management from a feminist ecological perspective. The hydrocarbon exploitation fundamental to these projects transforms women's roles in social reproduction and production, their relationship with nature, and their dependence on state‐institutionalized energy regimes. We examine changes in women's territorially based work of care at sites in Ecuador's petroleum circuit. An ethnographic focus on the transformation of women's daily lives at sites of petroleum exploration, exploitation, and processing in Ecuador reveals an often overlooked dimension of the socioenvironmental conflicts produced by the intensification of national economic insertion into the global energy market. This article thus examines the intersection of state development policies and the gendered construction of subjects of development. The exploitation of natural resources transforms the meanings and values of nature and development, of women's work of care, and of the participation of these in different energy regimes.